Lighting installation of a parking lot as a source of light pollution - Ściężor, Tomasz; Czaplicka, Anna (Instal, 2023)
Parking lots, often of a large area, are becoming a typical element of the landscape of modern cities and their surroundings. They can be found both at shopping malls, within office complexes or near communication centres. Illumination of their surface must ensure, above all, the protection of parked vehicles and their users, but also minimally interfere with the natural environment. As part of the research, an analysis of the lighting of a parking lot in one of the office complexes in Katowice, as well as a complex of parking lots surrounding one of the shopping centres in Krakow, was carried out. In both cases, the proper construction of all the light sources used was found. The phenomenon of glare related to the illumination of neighbouring buildings was found. However, the main problem is the presence of underexposed areas, which is related to both the incorrect spatial distribution of the lamps used, as well as the shielding of part of the lighting by various types of terrain objects, such as billboards or trees.
Keywords: light pollution; artificial lighting; parking lots; shopping malls